VDC_100102370977.0X000001. Issue 5 (May 2018) - Gelbard, Rondi; Khor, Desmond; Inaba, Kenji; Okoye, Obi; Szczepanski, Crystal; Matsushima, Kazuhide; Strumwasser, Aaron; Rhee, Peter; Demetriades, Demetrios
Mirizzi syndrome (MS) is an uncommon complication of cholelithiasis caused by extrinsic biliary compression by stones in the gallbladder infundibulum or cystic duct. The purpose of this study was to evaluate the outcomes associated with a laparoscopic approach to this disease process. This is a 10-year, retrospective study conducted at two academic medical centers with established acute care surgery practices. Patients with a diagnosis of MS confirmed intraoperatively were included. Eighty-eight patients with MS were identified with 55 (62.5%) being type 1. Twenty six (29.5%) patients, all type 1, underwent successful laparoscopic cholecystectomy. Of the 62 patients that underwent open cholecystectomy, 27.3 per cent had a laparoscopy converted to open procedure. There was no significant difference in overall complications (19.2 vs 29%) among those undergoing laparoscopic versus open cholecystectomy. Length of stay was lower in patients that had a laparoscopic approach ( P = 0.001). Laparoscopic cholecystectomy can safely be attempted in type 1 MS and seems to be associated with fewer overall complications and shorter length of stay compared with an open approach.